Dzawadi - Webster, Gloria Cranmer (Anthropologica, 2022)
A member of the smelt family, the eulachon has been highly prized by the people of the Northwest Coast of North America for hundreds of years. The eulachon is harvested and processed to produced a rich oil, commonly called "grease." As eulachon spawn only in a few rivers, this resource is accessible only to those owners of those rivers. The oil was a valued trade item'in traditional times. On the coast, there are a number of well-documented "grease trails" along which various tribes, both coast and interior, would travel to trade. On the central coast of British Columbia, people from a number of villages make the annual spring trek to Dzawadi at the head of Knight Inlet during eulachon spawning time. This paper describes past and present fisheries at that site, with references to the impact of development, including clear-cut logging and commercial fishing for other species in the area.